Kinship, gender and the spiritual economy in medieval Central European Towns. Issue 2 (15th March 2021) - Lutter, Christina; Frey, Daniel; Krammer, Herbert; Majorossy, Judit
ABSTRACT: The present contribution starts from the debate about kinship as a social institution in medieval Europe initiated by Jack Goody's pioneering anthropological work in the 1980s and drawn upon by historians and anthropologists alike. We focus on the aspect of the allegedly systematic separation of kinship from the organization of memory of the dead brought about by the establishment of Christianity. However, throughout the European Middle Ages families did not completely cede memorial tasks to religious institutions. Rather, they re-affirmed memorial bonds to religious institutions by legal arrangements and through family members within these communities, just as kinship continued to play a key role in medieval political organization. Given their social heterogeneity medieval cities provide a rich documentation of networks across ties of family, kinship, friends, and clients that intersected with more institutionalized communities (parish churches, monasteries, hospitals). People bestowed economic benefits on these communities in return for their members' "eternal" prayer for the donators' souls. This created mutual bonds both between kin and religious communities. The ensuing forms of belonging were part of a more complex frame of social exchange, as families used the same institutions as "hubs" to corroborate social and political relations to their peers. These bonds would intersect with ties between representatives of kin groups with positions in key political organizations such as city councils. A further clue to understanding these relations is gender. Economic transactions and related memorial practices feature a considerable number of female actors underlining the salience of bilateral kin relations and practices of property devolution.